Jiangzhi Granule Ameliorates JNK-Mediated Mitochondrial Dysfunction to Reduce Lipotoxic Liver Injury in NASH - Jiang Y; Xu J; Ding J; Liu T; Liu Y; Huang P; Wang Q; Zheng P; Song H; Yang L (Diabetes, Metabolic Syndrome and Obesity)
Yuwei Jiang,1,* Jiaoya Xu,1,2,* Junyao Ding,1,* Tao Liu,1 Yang Liu,1,3 Ping Huang,1 Qianlei Wang,1 Peiyong Zheng,1 Haiyan Song,1 Lili Yang1 1Institute of Digestive Diseases, Longhua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Gout, Guanghua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Teaching Experiment Center, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haiyan Song; Lili Yang, Institute of Digestive Diseases, Longhua Hospital, Shanghai University of Traditional Chinese Medicine, 725 South Wanping Road, Shanghai, 200032, People’s Republic of China, Email songhy@126.com; yanglili76@126.comPurpose: Mitochondrial dysfunction mediated by c-Jun N-terminal kinase (JNK) plays an important role in lipotoxic liver injury in nonalcoholic steatohepatitis (NASH). This study aims to investigate the pharmacological mechanism of Jiangzhi Granule (JZG), a Chinese herbal formula against NASH, with a focus on its regulation of JNK signaling-mediated mitochondrial function.Methods: Hepatocytes were induced by palmitic acid (PA) for 24 h to establish an in vitro lipotoxic model, which was simultaneously treated with either JZG or vehicle control. Male C57BL/6J mice were fed a high-fat diet (HFD) for 22 weeks and then treated with JZG via gavage for additional 8 weeks. Lipotoxic injury in hepatocytes or mice liver tissues, as well as JNK signaling-related molecules, were further investigated.Results: JZG improved PA-induced lipid deposition, cell viability, apoptosis, and mitochondrial dysfunction in hepatocytes. In NASH mice, JZG reduced hepatosteatosis, and inflammatory infiltration, and improved mitochondrial morphology and quantity in liver tissues. Additionally, elevated phosphorylation ratio of non-receptor tyrosine kinase c-Src (Src) and reduced phosphorylation ratio of JNK and SH2-containing protein tyrosine phosphatase (SHP-1) were found in both hepatocytes and mice liver tissues treated with JZG versus those with the vehicle.Conclusion: Taken together, JZG could improve mitochondrial dysfunction and reduce lipotoxic liver injury in NASH in vivo and in vitro models. The inhibition of the JNK signaling pathway may contribute to the underlying mechanism of JZG in preventing and reversing NASH development. Keywords: nonalcoholic steatohepatitis, Jiangzhi Granule, c-Jun N-terminal kinase, mitochondrial dysfunction, lipotoxic injury